Fabrication of a 2.4 GHZ XBEE wireless communication system with sent data to support the measurement of the tipping vessel rainfall at the BMKG Sicincin - Risa Noviarti; Asrizal Asrizal; Yohandri Yohandri (PILLAR OF PHYSICS, 2017)
Information of rainfall is required in agricalture to determine kind of plant wich is suitable planted in certain area. A rain gauge had used in BMKG Sicincin wastipping bucket raingauge model TB3-0.2 serial no.92-459. This rain gauge can not be used because its data loggeris damage.  Based on reality, researcher was interested to give solution by making wireless communication XBee in this rain gauge for sending data to PC. The goal of this research is to explain performance and design specification of system. Kind of this research is engineering research. Measurement technique and collecting data was executed by directly and indirectly measurement. Directly measurement was used to measure output of sensor and time of count. Indirectly measurement was used to determine accuration and precision of rain gauge. The data was analysed by using descriptive statistic and graph method. Mechanic part of system consist of tube, funnel and tipping bucket , while electronic part of system consist of sensor circuit, microcontroler circuit, RTC circuit, transmitter circuit and receiver sircuit. Precision of rain gauge in laboratory testing is 0.86, its average of accuration is 0.93 andrelative precision data transmition is 1. Accuration ofrain gauge in field testingis 0.92